Management styles and the coaches` self-evaluation in women`s handball teams - Mikalauskas, R. (Education. Physical training. Sport, 2000)
Management, while applying a certain method of the activity, is an action which gets people closer and helps them to achieve their aims. The formation of the rational management style in a team is a complex action, demanding from the coaches permanent work in educating athletes, as well as self-education. The aim of the research is to determine the management style of coaches in Lithuanian women`s handball league. Women`s team coaches and their assistants took part in this research. The research has shown that the prevailing management style of the coaches in women`s handball teams is democratic with a high degree of manifestation. The application of the self-evaluative methods has made it possible to ascertain that coaches idealize their activities, understand themselves realistically and do not pay enough attention to that sphere of influence which could help to influence other people.